(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Electronic media use may affect sleep health. The present study aimed to estimate the association between technological devices usage, especially mobile phone, during the evening/night and self-reported sleep disorders. Methods: The survey was conducted between June and September 2016. Anonymous self-reported questionnaire was distributed to the Italian general population and investigated demographic data, presence of sleep disorders and the use of electronic devices. Results: The analysis was based on 597 questionnaires. Mobile phone exposure has been associated with increased difficulty falling to sleep (p= 0.018). The use of mobile phones at bedtime was significantly related to self-reported sleep disturbance (p <0.001). Using mobile phone more than 60 minutes before going to sleep, the use of these devices in bed, surfing internet remained statistically significant in the multivariate analysis. Conclusion: Our results suggest that the use of a mobile phone before going to sleep is associated with reporting sleep disturbances. Public health prevention strategies could comprise promotion of optimum sleep habits and information regarding the effects of an intensive electronic devices use on the sleep status.